Power Ultrasound- and Organic Acid-Based Hurdle Technology to Reduce Listeria monocytogenes and Salmonella enterica on Whole Apples and Peaches - Bashayer A. Khouja; Hina Mathias; Mayura Joshi; Megan L. Fay; Supriya Korade; Catherine W. Y. Wong; Diana S. Stewart; Xinyi Zhou; Wei Zhang; Joelle K. Salazar (Foods)
Fresh produce, such as peaches and apples, are agricultural commodities, making them susceptible to contamination by foodborne pathogens such as Listeria monocytogenes and Salmonella enterica. Traditional methods, such as chlorine washes, have limitations related to antimicrobial efficacy, prompting interest in alternative techniques, such as power ultrasound. This study evaluated the use of power ultrasound, alone and combined with organic acids (citric, lactic, and malic), to reduce pathogen populations on whole apples and peaches. Pathogen cocktails of L. monocytogenes and S. enterica were spot-inoculated on fruit surfaces at an initial population level of 8–9 log CFU/fruit. The fruits were then submerged in water or citric, malic, or lactic acid at concentrations of 1%, 2%, or 5% alone or with power ultrasound treatment at 40 kHz for 2, 5, or 10 min. Results revealed that treatment conditions on apples exhibited significantly greater pathogen reduction than on peaches, likely due to the smoother surface topology on apples compared to the rougher, trichome-covered peach surfaces. Between the two pathogens, L. monocytogenes exhibited significantly greater resistance to treatments, resulting in maximum reductions of approximately 4 log CFU/fruit. In contrast, treatments were more effective against S. enterica, as lactic acid alone reduced S. enterica populations by >6 log CFU/fruit. Malic acid was the second-most effective organic acid against S. enterica, leading to >4 log CFU/fruit reduction. Synergistic antimicrobial effects were observed when organic acids were used in combination with power ultrasound. For instance, an additional reduction of 2–3 log CFU/fruit was achieved for S. enterica compared to the use of organic acid treatments alone. These findings support the use of organic acid and power ultrasound in hurdle as an effective strategy to mitigate foodborne pathogen risks on whole fruits such as apples and peaches. Further research would be helpful to optimize and validate such hurdle treatments for inactivating a broader spectrum of microbial pathogens on diverse produce surfaces.